Soil microbiota promote the success of the perennial legume Lupinus polyphyllus more strongly in invasive than in native populations - Nylund, Annika; Kalske, Aino; Mousavi, Seyed Abdollah; Ramula, Satu (Oxford University Press (OUP), 2026)
Background and Aims
Geographical variation in soil microbial communities can give rise to differences in the performance and competitive abilities of plants between the invasive and native ranges, potentially due to the presence of more efficient mutualists or release from pathogens in the invasive range.
Methods
We investigated how microbial inoculation with soil taken from invasive and native sites of the legume Lupinus polyphyllus affects the performance of plants of both origins and their below-ground bacterial communities. We also exposed a co-occurring herb from the invasive range to a substrate that had previously been occupied by inoculated and non-inoculated L. polyphyllus to assess whether soil microbes mediate its competitive allelopathic effects.
Key Results
We found that for plants of invasive origin, inoculation with soil from the invasive range enhanced performance more than inoculum from the native range. For plants of native origin, instead, performance was facilitated equally by the microbiota from both ranges. Substrate that had been occupied by L. polyphyllus did not inhibit the germination of the co-occurring herb. Differences in the composition of the below-ground bacterial communities between plants grown in soil inocula from invasive and native sites at the family level were minor.
Conclusions
Our results advance the mechanistic understanding of plant invasions, suggesting that soil mutualists in the invasive range may facilitate invasion success as proposed by the enhanced mutualism hypothesis. Alternatively, greater performance of invasive plants with soil microbes from their own range could reflect other adaptations either in plants or soil microbiota, or in both.